2001
DOI: 10.1103/physreve.65.016606
|View full text |Cite
|
Sign up to set email alerts
|

Observation of breather resonances in Josephson ladders

Abstract: We report experimental observation of resonances excited by nonlinear localized states (rotobreathers) in Josephson junction ladders. The rotobreathers are found to persist in a frequency range that allows for their resonant interaction with linear electromagnetic modes in the ladders. This interaction leads to nearly constant voltage steps on the current-voltage characteristics. We also present numerical simulations that agree well with experimental data and confirm the resonant interaction between breathers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 16 publications
4
17
0
Order By: Relevance
“…58) showed very good qualitative agreement with experiments [361]. In addition numerical studies allow one to directly access the tricky details of the nonlinear dynamics of the obtained states.…”
Section: Resonances With Cavity Modessupporting
confidence: 67%
“…58) showed very good qualitative agreement with experiments [361]. In addition numerical studies allow one to directly access the tricky details of the nonlinear dynamics of the obtained states.…”
Section: Resonances With Cavity Modessupporting
confidence: 67%
“…Moreover, a breather state may be tuned into resonance with other dynamical modes of the system which leads to an increasing complexity of the breather dynamics. Experimental studies revealed a whole "zoo" of different breather states, instabilities, resonances and switching scenarios depending on the parameters of the ladder [7][8][9][10][11]. Similar features have been found in numerical simulations.…”
Section: Introductionsupporting
confidence: 64%
“…The I -V characteristics of a breather (11) differs from that of the HWS which is γ = Vα. The breather is characterized by a smaller voltage drop across the resistive vertical junction for a given current value γ .…”
Section: Breather Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…After these works more experiments were done and the results reported on various publications. [12][13][14][15][16][17] Experiments at MIT 2 were done in open ladders with nine vertical junctions ͑see Fig. 6͒.…”
Section: The Experimental Detectionmentioning
confidence: 99%